(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In light of WHO’s declaration that obesity is a global epidemic, the term "globosity" was coined. Obesity encourages a series of secondary illnesses, such as metabolic syndrome, hyperlipidemia, inflammation, thrombosis, hypertension, and diabetes. Modern medicine treats obesity with synthetic pharmaceuticals, bariatric procedures, various fasting techniques, the ketogenic diet, etc., many of which have long-term side effects. As a result, it is unable to treat obesity without causing any negative side effects. Particularly, the Keto diet has been demonstrated to effectively reduce weight, but it also has adverse effects. In Ayurveda, a variety of approaches and enough attention have been focused on managing Sthaulya (obesity) in the form of dietary guidelines, diverse Aharvarga (food groups), Pathya-apathya, etc. One of them Mamsa varga (meat and its preparation), Gorasa varga (milk and its preparation), and Shimbi dhanya varga (classification of pulses) are some of the foods that are crucial in reducing the negative effects of the keto diet and improving the results of a high-fat, moderate-protein diet protocol.